An electrospinning membrane biomaterial and its anti-inflammatory activity application

Through polyvinyl alcohol (PVA)/citric acid (CA)/sulfated glucomannan (DS-0.164) electrospinned membrane biomaterial, the problem of difficulty in healing wounds in diabetic patients is solved, and the anti-inflammatory effect of non-cytotoxicity and effective inhibition of the expression of proinflammatory factors is achieved, and a safe and effective dressing material is provided.

CN119236148BActive Publication Date: 2025-04-04JINAN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411765234.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-04
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Due to long-term hyperglycemia and high inflammatory states, macrophages are activated and pro-inflammatory cytokines are continuously produced, making it difficult for the wound to heal. Existing dressing materials are cytotoxic, limiting their bioavailability.

Method used

Polyvinyl alcohol (PVA)/citric acid (CA)/sulfated glucomitan (DS-0.164) electrospinning membrane biomaterial was used to prepare membrane-like materials through electrospinning technology, using sulfated glucomitan as a supported polysaccharide, polyvinyl alcohol as a polymer substrate, and citric acid as a crosslinking agent to form a non-cytotoxic anti-inflammatory material.

Benefits of technology

This material can effectively inhibit the expression of proinflammatory factors in M1 macrophages, reduce the inflammatory response, and provide a safe and effective dressing material to promote wound healing in diabetic patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236148B_ABST
    Figure CN119236148B_ABST
Patent Text Reader

Abstract

The invention discloses a kind of electrostatic spinning membrane biomaterial, relates to the field of biotechnology, and the electrostatic spinning membrane biomaterial is prepared with sulfated konjac glucomannan as load polysaccharide, polyvinyl alcohol as polymer substrate, and citric acid as cross-linking agent. The biomaterial prepared by the present invention has good physical properties, shows good effect of suppressing the overexpression of related proinflammatory factors, and can be used as an auxiliary material for chronic inflammatory wounds of diabetic patients. It has the following advantages: 1. Glucomannan is a polysaccharide extracted from araceae plant konjac, has good biocompatibility, good film-forming property, and is a good auxiliary drug for diabetes; 2. By cell verification, the prepared sulfated glucomannan is non-toxic, PCS-0.4 film can load macrophages, and has a significant inhibitory effect on the expression of M1 type macrophage proinflammatory factors; 3. The preparation method is simple, and the substrate and cross-linking agent used are green compounds, with good safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biotechnology, and more specifically to a polyvinyl alcohol (PVA) / citric acid (CA) / sulfated glucomannan (DS-0.164) electrospinning membrane biomaterial and its anti-inflammatory activity application. Background Art

[0002] M0 macrophages are a type of immune cell widely distributed in tissues throughout the body. They participate in immune regulation, phagocytosis and antigen presentation, and play an important role in the body's immune defense, immune homeostasis and immune surveillance. They can be induced into M1 macrophages by cytokines such as interferon-γ (IFN-γ) and lipopolysaccharide (LPS), producing proinflammatory cytokines such as IL-6 and TNF-α. On the other hand, M2 macrophages activated by cytokines such as IL-4 produce anti-inflammatory responses by secreting anti-inflammatory cytokines such as IL-10, and participate in tumor angiogenesis and extracellular matrix remodeling.

[0003] Diabetic patients are in a state of high blood sugar and high inflammation for a long time. The macrophages in their wounds are activated for a long time, and they continue to produce a large number of pro-inflammatory cytokines, which makes it difficult for the wound to heal. In the existing technology, dressings for diabetic patients mostly use cross-linking agents such as glutaraldehyde and genipin, which have certain cytotoxicity and limit their bioavailability.

[0004] Therefore, providing a material that is non-cytotoxic and can inhibit the expression of pro-inflammatory cytokines as a wound dressing for diabetic patients is an urgent problem that needs to be solved by those skilled in the art. Summary of the invention

[0005] In view of this, the present invention provides a polyvinyl alcohol (PVA) / citric acid (CA) / sulfated glucomannan (DS-0.164) electrospinning membrane biomaterial and its anti-inflammatory activity application.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] An electrospinning membrane biomaterial is prepared by taking sulfated glucomannan as a loaded polysaccharide, taking polyvinyl alcohol as a polymer base and taking citric acid as a cross-linking agent.

[0008] The main raw material used in the present invention is low-cost glucomannan, which, as dietary fiber, is a good auxiliary drug for diabetes. The source of the electrospun biomaterial of the present invention is clear, all of which are green raw material bases, and have repeatability and controllability. The biomaterial has good affinity with macrophages, does not cause the production of proinflammatory factors under normal conditions, and can inhibit the secretion of proinflammatory factors of M1 macrophages under inflammatory conditions, effectively reducing the occurrence of inflammatory reactions.

[0009] Another object of the present invention is to provide a method for preparing the above-mentioned electrospinning membrane biomaterial, comprising the following steps:

[0010] S1: dissolving glucomannan in N,N-dimethylformamide, slowly stirring and adding chlorosulfonic acid dropwise under ice-salt bath conditions; the volume mass ratio of chlorosulfonic acid to glucomannan is (1-5):1;

[0011] Heat to reflux at 70°C for 6 h, adjust the pH to 7, add 3 times the amount of acetone in the reaction system, and place at 4°C for precipitation overnight;

[0012] The precipitate was dissolved in deionized water, dialyzed for 3 days using a 3500 Da dialysis bag, and freeze-dried to obtain sulfated glucomannan;

[0013] S2: dissolving polyvinyl alcohol, citric acid and sulfated glucomannan in deionized water, stirring at 60°C for 1 h, to obtain a PCS-film spinning solution; the mass ratio of the polyvinyl alcohol, citric acid and sulfated glucomannan is 60:12:(1-4);

[0014] The PCS-film spinning solution was electrospun, then vacuum dried, thermally cross-linked at 120°C for 2h, and the electrospun membrane was peeled off and flattened.

[0015] Preferably, the volume mass ratio of chlorosulfonic acid to glucomannan in S1 is 3:1.

[0016] Preferably, the mass ratio of polyvinyl alcohol, citric acid and sulfated glucomannan in S2 is 30:6:1.

[0017] Preferably, the electrospinning method described in S2 is to suck the PCS-film spinning solution into a syringe, and connect it to a micro pump after exhausting air bubbles; fix the needle and the injection device above the receiving plate, connect the positive electrode of the electrospinning device to the needle, and connect the negative electrode to the tin foil flat plate as the receiving device;

[0018] The electrospinning parameters are: needle 19 G, voltage +15 kV, -6 kV, receiving distance 15 cm, flow rate 0.5 mL / h, temperature 28°C, humidity 56%

[0019] Another object of the present invention is to provide the use of the above electrospinning membrane biomaterial or the biomaterial prepared by any of the above methods in the preparation of wound dressing materials for diabetic patients.

[0020] Beneficial effects: The electrospun membrane PCS-0.4 film prepared by the present invention uses sulfated glucomannan as the loaded polysaccharide, polyvinyl alcohol as the polymer substrate, and citric acid as the cross-linking agent. It has good physical properties and shows a good effect of inhibiting the overexpression of related pro-inflammatory factors. It can be promoted and applied as an adjuvant for chronic inflammatory wounds in diabetic patients. It has the following advantages: 1. Glucomannan is a polysaccharide extracted from the Araceae plant konjac, which has good biocompatibility and good film-forming properties. It is a good auxiliary drug for diabetes; 2. Through cell verification, the prepared sulfated glucomannan is non-toxic, PCS-0.4 film can load macrophages, and has a significant inhibitory effect on the expression of pro-inflammatory factors in M1 macrophages; 3. The preparation method is simple, and the substrate and cross-linking agent used are both green compounds with good safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0022] Figure 1 The attached figure is a standard curve of sulfate.

[0023] Figure 2 The attached figure shows the Fourier transform infrared spectrum scanning result of sulfated glucomannan (SKGM).

[0024] Figure 3 The attached figure shows the cytotoxicity test results of SKGM with different substitution degrees.

[0025] Figure 4 The attached figure shows the Fourier transform infrared spectrum scanning results of PCS-film electrospun membrane.

[0026] Figure 5 The attached figure shows the scanning electron microscopy results of PCS-film electrospinning membrane (10000×).

[0027] Figure 6 The attached figure shows the test results of mechanical properties of PC-film electrospun membrane.

[0028] Figure 7 The attached figure shows the mechanical properties test results of PCS-film electrospun membrane (0.2 wt% DS-0.164).

[0029] Figure 8 The attached figure shows the mechanical properties test results of PCS-film electrospun membrane (0.4 wt% DS-0.164).

[0030] Fig. 9 The attached figure shows the mechanical properties test results of PCS-film electrospun membrane (0.8 wt% DS-0.164).

[0031] Fig.10 The attached figure shows the contact angle test results of PCS-film electrospinning membrane.

[0032] Fig.11 The attached figure shows the results of macrophage adhesion of PCS-film electrospinning membrane, where **** represents P ≤ 0.0001.

[0033] Fig.12 The attached figure shows the results of PCS-film electrospinning membrane inhibiting the expression of inflammatory factors, where * represents P≤0.05; ** represents P≤0.01; **** represents P≤0.0001.

[0034] Fig.13 The attached figure shows the coagulation test results of SKGM with different substitution degrees.

[0035] Fig.14 The attached figure shows the coagulation test results of PCS-film electrospinning membrane. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The embodiments of the present invention disclose a polyvinyl alcohol (PVA) / citric acid (CA) / sulfated glucomannan (DS-0.164) electrospinning membrane biomaterial and its anti-inflammatory activity application. The raw materials involved in the present invention are all commercially available, and their sources are not specifically limited. The methods involved, unless otherwise specified, are all conventional methods and will not be described one by one here.

[0038] Example 1 Preparation of sulfated glucomannan (SKGM)

[0039] 1. Preparation method: 80 mL of N,N-dimethylformamide (DMF) and 1 g of KGM were placed in a 250 mL three-necked flask. Under an ice-salt bath (ice: sodium chloride mass ratio is 3:1), chlorosulfonic acid was slowly stirred and added dropwise (the volume mass ratio of chlorosulfonic acid: KGM was 1:1, 3:1, and 5:1). After heating and reflux at 70°C for 6 h, the pH was adjusted to 7 with 10% sodium hydroxide, and 3 times the amount of acetone in the reaction system was added, and the mixture was placed at 4°C for precipitation overnight. The precipitate was dissolved in 100 mL of deionized water, dialyzed with a 3500 Da dialysis bag for 3 days, and freeze-dried to obtain sulfated KGM (SKGM). It was determined that the yields of sulfated KGM in the three ratios (SKGM-1:1, SKGM-3:1, and SKGM-5:1) were 20%, 87.5%, and 50%, respectively.

[0040] 2. SKGM product identification

[0041] (1) Determination of SKGM sulfate substitution degree:

[0042] Establishment of sulfate standard curve: Take potassium sulfate and dry it to constant weight, weigh 108.15 mg and put it into a 100 mL volumetric flask, add 1 mol / L hydrochloric acid to make up to the scale to prepare a 0.6 mg / mL sulfate standard solution, take 60 μL, 180 μL, 300 μL, 420 μL, 540 μL, and 600 μL into 7 mL centrifuge tubes, continue to add 1 mol / L hydrochloric acid to make up to 1 mL, and obtain sulfate standard solutions with contents of 36 μg, 108 μg, 180 μg, 252 μg, 324 μg, and 360 μg, respectively. Do it in parallel for groups A1 and A2.

[0043] Prepare 0.5% gelatin (GE) solution, 0.5% gelatin (GE) / 1% barium chloride (BaCl) solution in deionized water. 2 ) solution and 8% trichloroacetic acid (TCA) solution.

[0044] Add 3.5 mL of 8% TCA solution to groups A1 and A2, and 1 mL of 0.5% GE / 1% BaCl to group A1. 2 The A2 group was added with 1 mL of 0.5% GE solution, mixed thoroughly and allowed to stand for 20 min, and the absorbance at 360 nm was measured. 1 mol / L HCl was used as the blank. After deducting the blank, the (A1-A2) value was used as the ordinate and the concentration of the sulfate standard solution was used as the abscissa to draw a sulfate standard curve (see Appendix). Figure 1 ).

[0045] Determination of sulfuric acid substitution degree: Take SKGM and prepare a 1 mg / mL sample solution with 1 mol / L HCl. Stir at 100℃ for 6 h to fully hydrolyze it with acid to obtain a filtrate. Take 4 mL of the filtrate, and take 2 mL of each of the parallel A1 and A2 groups. After adding 3.5 mL of 8% TCA solution to groups A1 and A2, add 1 mL of 0.5% GE / 1% BaCl2 solution to group A and 1 mL of 0.5% GE solution to group A2. After fully mixing and standing for 20 min, measure the absorbance at 360 nm, and substitute the (A1-A2) value into the standard curve to calculate the sulfate content (see Table 1).

[0046] The calculation formula of substitution degree is:

[0047] Among them, DS is the degree of substitution of sulfate groups in SKGM, S% is the content of sulfate groups, and SKGM is named according to DS.

[0048] Table 1 SKGM substitution degree

[0049]

[0050] As shown in Table 1, the degree of substitution of SKGM-1:1 is 0.004, named DS-0.004, the degree of substitution of SKGM-3:1 is 0.164, named DS-0.164, and the degree of substitution of SKGM-5:1 is 0.330, named DS-0.330. As the amount of chlorosulfonic acid added increases, the DS value increases.

[0051] (2) Identification of SKGM organic functional groups:

[0052] The potassium bromide tablet method was used. 2 mg of KGM, DS-0.004, DS-0.164 and DS-0.330 were weighed into an agate mortar. 400 mg of dry potassium bromide (sample: potassium bromide mass ratio was 1:200) was added and mixed and ground evenly. The mixture was pressed into a tablet with a diameter of 0.5 cm using a tablet press. The sample was placed in a Fourier transform infrared spectrometer for scanning. The wavelengths of 4000-400 cm -1 Absorption values ​​within a wavelength range.

[0053] As attached Figure 2 As shown, COS was observed at 620 cm -1 、818-826 cm -1 The peaks are in the range of 1237 cm-1 and 1237 cm-2 for S=O. -1 , 1150 cm -1 The peaks are in the range of 997-1012 cm -1The peaks appeared in the range of 40.44 nm and 1.34 nm, indicating that DS-0.004, DS-0.164 and DS-0.330 were successfully connected with sulfate groups.

[0054] (3) Exploration of cytotoxicity of SKGM with different degrees of substitution:

[0055] Set up sample groups DS-0.004, DS-0.164, DS-0.330 and a control group (Control). Take mouse macrophage RAW264.7 cells and count them at 8×10 3 / well, 100 μL / well cells were inoculated in 96-well plates, and after culturing in a carbon dioxide constant temperature incubator for 24 h, each group was added with 100 μg / mL, 50 μg / mL, and 25 μg / mL sample concentrations, and the control group was added with DMEM complete medium and continued to culture for 24 h. The next day, the cell culture medium was discarded, and MTT solution with a working concentration of 0.5 mg / mL was added, and cultured for 4 h in the dark; the MTT solution was discarded, DMSO was added at 150 μL / well, and the plate was shaken at 37°C and 360 rpm for 10 min, and the absorbance was measured at 570 nm.

[0056] As attached Figure 3 As shown, the cell survival rates of DS-0.164 and DS-0.330 were both above 85% at 25-100 μg / mL, and could reach over 95% at low concentrations. They were non-cytotoxic, compatible and safe with RAW264.7 cells, and the cell survival rate of DS-0.004 was maintained at around 80%, so DS-0.004 was excluded from subsequent experiments.

[0057] Example 2 Preparation of PVA / CA / DS-0.164 electrospun membranes (PCS-films)

[0058] 1. Preparation method

[0059] Preparation of spinning solution: 0.6 g polyvinyl alcohol (PVA), 0.12 g citric acid (CA) and an appropriate amount of DS-0.164 SKGM sample were weighed and dissolved in 5 mL deionized water, placed in a constant temperature water bath at 60°C and magnetically stirred for 1 h to obtain PCS-film (0.2 wt% DS-0.164), PCS-film (0.4 wt% DS-0.164) and PCS-film (0.8 wt% DS-0.164) spinning solutions. A SKGM blank control group was also set up (0.6 g polyvinyl alcohol (PVA) and 0.12 g citric acid (CA) were weighed and dissolved in 5 mL deionized water, placed in a constant temperature water bath at 60°C and magnetically stirred for 1 h to obtain PC-film spinning solution, which was a transparent viscous liquid with a certain fluidity).

[0060] Preparation of PCS-films: Take an appropriate amount of sample spinning solution and inhale it into the syringe. After exhausting the air bubbles, connect it to the micro pump. Fix the needle and the injection device above the receiving plate, connect the positive electrode of the electrospinning device to the needle, and the negative electrode to the tin foil flat plate as the receiving device. The optimal conditions for electrospinning obtained through preliminary experiments are shown in Table 2 below, namely: needle 19G, voltage +15 kV, -6 kV, receiving distance 15 cm, flow rate 0.5 mL / h, temperature 28°C, humidity 56%. Place the receiving tin foil in a vacuum heating drying oven. After thermal crosslinking at 120°C for 2 h, gently peel off the electrospun membrane with tweezers, place it in a drying container, and flatten it for storage.

[0061] Table 2 Optimal conditions for electrospinning

[0062]

[0063] 2. PVA / CA / DS-0.164 electrospinning membrane performance evaluation

[0064] Determination of organic functional groups of PCS-films: potassium bromide tableting method was used. Appropriate amounts of PC-film and PCS-films were weighed in an agate mortar. Dry potassium bromide (sample: potassium bromide mass ratio was 1:200) was added and mixed and ground evenly. The mixture was pressed into a tablet with a diameter of 0.5 cm using a tablet press. The sample was placed in a Fourier transform infrared spectrometer for scanning and the wavelengths of 4000-400 cm were detected. -1 Absorption values ​​within a wavelength range.

[0065] As attached Figure 4 As shown, the 615 cm -1 COS peak appears at 1242 cm -1 、1239 cm -1 The peak shape of SO at 1087 cm -1 、1093 cm -1 The peak shape changes significantly.

[0066] Surface morphology analysis of PCS-films: Take a 1 cm × 1 cm film sample and stick it directly on the conductive glue, and use a Quorum SC7620 sputtering coater with a gold spraying rate of 10 mA; then use a TESCAN MIRA LMS scanning electron microscope to photograph the sample morphology and other tests, and the acceleration voltage is 3 kV when photographing the morphology. Figure 5 As shown, a nanonetwork structure with cross-pores was obtained without obvious beading phenomenon, and Image J analysis showed that the fiber diameter was within 240-500 nm.

[0067] Mechanical properties of PCS-films: According to the national standard GB / T 1040, PCS-films were cut into rectangles with a length of 20 mm and a width of 4 mm, and then the tensile properties (elastic modulus and elongation at break) of the electrospun membranes were measured using an electronic universal testing machine at a speed of 1 mm / min. Figure 6 -Attached Fig. 9 As shown in Table 3, PCS-film (0.4 wt% DS-0.164) has elastic modulus and elongation at break similar to those of PC-film.

[0068] Table 3 Mechanical properties of PCS-films

[0069]

[0070] Contact angle measurement of PCS-films: The electrospun PCS-films were cut into 1 cm × 1 cm rectangles, fixed flat on a glass slide, and the contact angle of the electrospun PCS-films was measured using a contact angle meter and a water drop shape analysis system. Fig.10 As shown in Table 4, the contact angle of PCS-film (0.4 wt% DS-0.164) can reach 58.6°-65°, which is suitable for cell adhesion and growth. Therefore, it was retained for subsequent experiments and referred to as PCS-0.4 film.

[0071] Table 4 Contact angle measurement of PCS-films

[0072]

[0073] Example 3 Determination of the anti-inflammatory effect of PVA / CA / DS-0.164 electrospun membrane

[0074] 1. Adhesion of macrophages RAW264.7 to PCS-films

[0075] Cell pretreatment and cell death and viability identification: PC-film of the control group and PCS-0.4 film of the sample group were cut into 1 cm × 1 cm squares and flattened in a 24-well plate filled with 75% ethanol. They were soaked overnight, the 75% ethanol was discarded, and the plate was opened for UV irradiation for 1 h. 500 μL PBS was added to each well and soaked at 37°C for 3-4 h. PBS was discarded. A blank group (Blank) was set up with 3 replicates in each group. Mouse macrophage RAW264.7 cells were counted and 7.5×10 5 / well, 0.5 mL / well was used to inoculate cells in PC-film and PCS-0.4 film. In the Blank group, only cells were inoculated without other treatments. After culturing in a carbon dioxide constant temperature incubator for 24 hours, Calcein AM / PI detection working solution was added at 250 μL / well according to the instructions of the Calcein / PI cell viability and cytotoxicity detection kit. After incubation at 37°C in the dark for 30 minutes, the adhesion of RAW264.7 cells was observed under an inverted fluorescence microscope and the proportion of live and dead cells was analyzed by Image J.

[0076] As attached Fig.11 As shown in the figure, RAW264.7 can adhere to PC-film and PCS-0.4 film. Compared with the Blank group, the number of adhered cells decreased, but the dead / live cell ratio was significantly lower than that of the Blank group after analysis by Image J software. This shows that PC-film and PCS-0.4 film are non-toxic, support the adhesion and growth of RAW264.7 cells, and have good cell compatibility.

[0077] 2. Expression of inflammatory factors in PCS-film (0.4 wt% DS-0.164)

[0078] Cell pretreatment and determination of inflammatory factors: The control group PC-film and sample group PCS-0.4 film were sterilized. A blank group (Control) and an inflammatory group (LPS / IFN-γ) (the secretion levels of IL-6, TNF-α and NO in this group were significantly higher than those in other groups) were set up, with 3 replicates in each group. Mouse macrophage RAW264.7 cells were counted and 1×10 5 / well, 0.5mL / well The cells were inoculated in a 24-well plate and cultured in a carbon dioxide constant temperature incubator for 24 h. Except for the Control group, 100 ng / mL LPS and 10 ng / mL IFN-γ were added to each well for stimulation for 24 h. The cell supernatant was collected and centrifuged at 2500 r / min for 3 min. The supernatant was taken and the expression levels were determined according to the instructions of the nitric oxide (NO) kit, mouse IL-6 ELISA kit and mouse TNF-α ELISA kit.

[0079] As attached Fig.12 As shown, PCS-0.4 film did not induce RAW264.7 (M0 type) cells to produce inflammatory factors, and inhibited the secretion of inflammatory factors NO, IL-6 and TNF-α in M1 type cells. Among them, PCS-0.4 film could significantly reduce the expression of TNF-α, which was significantly different from PC-film.

[0080] Example 4 Determination of coagulation effect of PVA / CA / DS-0.164 electrospun membrane

[0081] 1. Weigh 10g of sulfated glucomannan (SKGM) with different degrees of substitution, and set sodium heparin as the positive control group and saline as the negative control group. Add 2.5mL rabbit whole blood (containing 10% sodium citrate) and immediately add 60μL calcium chloride (0.25M) solution. Invert the test tube every 1min, record the coagulation status, and report the results after 30min. Set up 3 replicates for each group to observe the coagulation effect.

[0082] As attached Fig.13 As shown, compared with heparin and SKGM substituted with DS-0.330, DS-0.164 avoided the risk of bleeding within 30 min.

[0083] 2. Take the electrospun membrane PCS-film (0.2 wt% DS-0.164), PCS-film (0.4 wt% DS-0.164), and PCS-film (0.8 wt% DS-0.164) and cut them into 2 cm × 2 cm squares. Set heparin sodium as the positive control group and saline as the negative control group. Add 2.5 mL of rabbit whole blood (containing 10% sodium citrate) and immediately add 60 μL of calcium chloride (0.25 M) solution. Invert the test tube every 1 min, record the coagulation status, and report the results after 30 minutes. Set up 3 replicates in each group to observe the coagulation effect.

[0084] As attached Fig.14 As shown, compared with heparin, the static spinning membranes PCS-film (0.2 wt% DS-0.164), PCS-film (0.4 wt% DS-0.164), and PCS-film (0.8 wt% DS-0.164) all avoided the risk of bleeding within 30 min.

[0085] In summary, the present invention uses sulfated glucomannan as the loaded polysaccharide, polyvinyl alcohol as the polymer substrate, and citric acid as the cross-linking agent to prepare the electrospun membrane PCS-0.4 film, which has good physical properties, shows a good effect of inhibiting the overexpression of related proinflammatory factors, and can be promoted and applied as an adjuvant for chronic inflammatory wounds in diabetic patients. It has the following advantages: 1. Glucomannan is a polysaccharide extracted from the Araceae plant konjac, which has good biocompatibility and good film-forming properties, and is a good auxiliary drug for diabetes; 2. Through cell verification, the prepared sulfated glucomannan is non-toxic, PCS-0.4 film can load macrophages, and has a significant inhibitory effect on the expression of proinflammatory factors in M1 macrophages; 3. The preparation method is simple, and the substrate and cross-linking agent used are both green compounds with good safety.

[0086] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0087] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An electrospinning membrane biomaterial, characterized in that: The electrospinning membrane biomaterial uses sulfated glucomannan as a loaded polysaccharide, polyvinyl alcohol as a polymer base, and citric acid as a cross-linking agent to prepare a PCS-film spinning solution, and is obtained by electrospinning; The sulfated glucomannan is DS-0.164, which is prepared by sulfating chlorosulfonic acid and glucomannan in a mass volume ratio of 3:1; The PCS-film spinning solution is composed of polyvinyl alcohol, citric acid, sulfated glucomannan and deionized water; the mass volume ratio of the polyvinyl alcohol, citric acid and deionized water is 0.6g:0.12g:5ml; The proportion of the sulfated glucomannan in the spinning solution is 0.4 wt %.

2. The method for preparing the electrospinning membrane biomaterial according to claim 1, characterized in that: The following steps are involved: S1: dissolving glucomannan in N,N-dimethylformamide, slowly stirring and adding chlorosulfonic acid dropwise under ice-salt bath conditions; the volume mass ratio of chlorosulfonic acid to glucomannan is 3:1; Heat to reflux at 70°C for 6 h, adjust the pH to 7, add 3 times the amount of acetone in the reaction system, and place at 4°C for precipitation overnight; The precipitate was dissolved in deionized water, dialyzed for 3 days using a 3500Da dialysis bag, and freeze-dried to obtain sulfated glucomannan; S2: dissolving polyvinyl alcohol, citric acid and sulfated glucomannan in deionized water, stirring at 60° C. for 1 h, to obtain a PCS-film spinning solution; the mass volume ratio of the polyvinyl alcohol, citric acid and deionized water is 0.6 g:0.12 g:5 ml; The proportion of the sulfated glucomannan in the spinning solution is 0.4wt%; The PCS-film spinning solution was electrospun, then vacuum dried, thermally cross-linked at 120°C for 2h, and the electrospun membrane was peeled off and flattened.

3. The method for preparing electrospinning membrane biomaterial according to claim 2, characterized in that: The electrospinning method described in S2 is to suck the PCS-film spinning solution into a syringe, and connect it to a micro pump after exhausting air bubbles; fix the needle and the injection device above the receiving plate, connect the positive electrode of the electrospinning device to the needle, and connect the negative electrode to the tin foil flat plate as the receiving device; The electrospinning parameters are: needle 19G, voltage +15kV, -6kV, receiving distance 15cm, flow rate 0.5mL / h, temperature 28°C, humidity 56%.

4. Use of the electrospun membrane biomaterial according to claim 1 or the biomaterial prepared by any one of the methods of claims 2-3 in preparing wound dressing materials for diabetic patients.

Citation Information

Patent Citations

  • Nano-fiber dressing based on Cardlan polysaccharide and derivative thereof as well as preparation method and application of nano-fiber dressing

    CN118976133A

  • Preparing process of anticoagulant konjak glucomanan sulfate

    CN1543979A